Implementation of Original Local Government Revenue Policy in Tomohon City Regional Environment Service - Wellem, Yiska Marsia; Pangkey, Itje; Mokat, Jetty (Technium Social Sciences Journal, 2023)
Garbage and cleaning retribution in Tomohon City is one of the potential regional income or Original Local Government Revenues (PAD). Which is the collection process must be carried out optimally to optimize regional retribution receipts every year which will also improve cleaning services in the city of Tomohon. The Tomohon City Regional Environmental Service is the field that monitors the collection of garbage and cleaning fees. In its implementation, the acceptance of garbage and cleaning fees for the City of Tomohon in 2020 where 2020 has decreased due to the Covid-19 pandemic, besides that there are also obstacles in the collection process which has resulted in the process of collecting garbage and cleaning fees not being optimal carried out by the City Environment Service Tomohon. The purpose of the research conducted by researchers is to find out the efforts to optimize the collection of garbage and cleaning fees in Tomohon City, as well as to find out the obstacles in the process of collecting garbage and cleaning fees carried out by the Environmental Service. This study used qualitative research methods. Data collection techniques were carried out by means of interviews, observation, and documentation. The data analysis technique used is data reduction, data presentation, and conclusion. The results of the research conducted show that efforts to optimize the collection of garbage and cleaning fees carried out by the Tomohon City Environmental Service have never carried out sudden inspections in an effort to increase supervision, and have not been able to cooperate with other parties in the process of facilitating payments. Apart from that, there are still obstacles which are the lack of awareness of mandatory retribution. As for overcoming these obstacles, what can be done by the Tomohon City Environmental Service is to continue to socialize with the community/compulsory retribution and will also continue to improve the administration system to make it more effective.